The Teaching Practice of the Novice Elementary School Teacher upon Entering the Professional Service - Gómez-Solís, Myriam (2023)
The purpose of this article is to describe the difficulties in teaching practice, as well as the coping strategies, experienced by beginning elementary school teachers in Mexico upon entering the service. The study is qualitative with a hermeneutic phenomenological approach, which allowed us to rely on narratives obtained through semi-structured interviews of five novice teachers. The results are presented from a perspective of theories and beliefs of educational practice in four dimensions: school context, anticipation, conduction and evaluation of the teaching-learning process. It is identified that teachers download the lesson plans elaborated on the Internet, from which the difficulties in the three moments of teaching derive since planning is the starting point to anticipate experiences and guide the actions of intervention and evaluation. Regarding the coping strategies, they have the teaching experience as a reference.